Assessment of microplastic contamination in some commercial fishes of the southern Caspian Sea and its potential risks - Gholizadeh, Mohammad; Bagheri, Tahereh; Harsij, Mohammad; Danabas, Durali; Zakeri, Mohammad; Siddique, Mohammad Abdul Momin (Environmental science and pollution research international, 2024)
This study examined the occurrence of microplastics (MPs) in the gastrointestinal tract (GIT) of 384 fishes classified into four species from 11 sites in 2022 from the southern part of the Caspian Sea. GITs of fishes were collected and digested in H2O2 and KOH at 45 °C for 72 h. After filtration, extracted MPs were observed under a stereomicroscope, and selected MP particles were identified using FTIR. Presence of MPs was 68.98% in the GIT of the investigated fish. The mean abundance of MPs was 5.9 ± 0.9 MPs/GIT in Rutilus kutum, 9.2 ± 1.2 MPs/GIT in Chelon auratus, 3.6 ± 0.7 MPs/GIT in Alosa braschnikowi, and 2.7 ± 0.5 MPs/GIT in Vimba vimba. The predominant form of MPs was fiber (58.21%), followed by fragment (34.77%). Black (34.4%), white (19.07%), and blue (14.58%) were the most frequently detected colors of MPs. Overall, 6 MP polymers were identified, dominantly polypropylene (42.86%), polystyrene (17.86%), and cellophane (14.28%). The western part of the Caspian Sea (mostly tourist spots and urban areas) showed more MP pollution in fish compared to the eastern part. Polymer hazard index (PHI) revealed alarming microplastic contamination in the southern Caspian Sea. The PHI value of the present study showed that PES (PHI = 8403.78) and PS (PHI = 535.80) were "Extreme danger" and "Danger" risk categories, respectively.
Keywords: ryby; Marine fish; Plastics; plastické hmoty; Environmental Monitoring; Polymer risks; zvířata; Gastrointestinal tract; Caspian Sea; Kaspické moře; mikroplasty; monitorování životního prostředí; Fishes; peroxid vodíku; Water Pollutants, Chemical; Animals; Hydrogen Peroxide; Microplastics; chemické látky znečišťující vodu; Cyprinidae